Feedback and its relationship to educational motor behavior in increasing the number of successful attempts at the skill of scoring in Football (College of Basic Education Research Journal, 2026)
The research aims to identify the relationship between teacher feedback and the performance of Football scoring skills, The researchers hypothesized that there is a statistically significant relationship between teacher feedback and successful student attempts, as well as a statistically significant relationship between student learning behavior, skill performance, and successful attempts at scoring in the football, as well as the relationship between the student's educational behavior and successful attempts to the performance of Football scoring skills, Providing students with positive and negative feedback to correct their performance by the teacher, along with the accompanying effects on the student's performance in both successful and unsuccessful attempts, and on their evaluation of their skill performance in Football scoring. The relationship between the student’s educational behavior and these variables and the extent of the impact of this behavior on his technical performance of skills. In order to reach knowledge of the educational behavior of the student and the teacher, it is necessary to use one of the statistical methods for analysis and diagnosis of the events that occur during the lesson.At the end of the analysis, we stop to process and evaluate the extent of benefit from the lesson’s impact on the student’s skill preparation, which leads us to the goal of the lesson that influences the game, because the teaching process is affected by several factors. It is influenced by lesson variables, vocabulary, timing, lesson content, skill type, teaching methods and techniques, as well as available resources and the time allocated for instruction. External and internal feedback constitute essential elements in learning acquisition, development, and mastery, and are indispensable and accompany every step of the educational process, this depends on analyzing student and teacher behavior through research and consistent investigation of the quantitative and qualitative picture of educational behavior through regular observation systems to analyze and evaluate behavior.